(untitled) (Indian Journal of Animal Production and Management, 2014)
Three different estrous synchronization protocols were evaluated. Treatment included an injection of prostaglandin (PGF2α;1 ml VSM - Vulva-sub mucosal route) on palpation of CL; status of the estrous cycle was evaluated by rectal palpation and addition of gonadotropin releasing hormone (GnRH 2.5ml), fixed time insemination (FTAI) was done 72 h post PGF2α injection. Similar was the second protocol in which, in gonadotropin releasing hormone (GnRH; 2.5 ml.) 7 days addition to PGF2α ; 1 ml VSM administration and 9 days GnRH; 2.5 ml was administered 48 h post PGF2α ; 1 ml VSM injection and FTAI was done. For the third protocol, GnRH treated buffaloes were observed for 7 days and then PGF2α; 14 days injection and GnRH;16 days was administered and at the time of A.I. Three different groups of animals were maintained for three different protocols respectively. Statistical data analysis (using chi-square) showed that first and second protocol have been found significantly (P<0.05) better than third protocol used in field buffaloes of Rajasthan.